(untitled) (Castilla. Estudios de Literatura, 2020)
The present collaboration focuses on a detailed analysis of the peculiarities of Larrian humor. In the first place we proceed to look into Larra´s life circumstances for the basic ingredients that led to the formation on his skeptical character and his tendency to negativity. Secondly we demonstrate how his skepticism and bitter vision of life are breeding ground for a humorous language as ingenious, subtle and insightful as acidic, corrosive and rough. In a third section we proceed with the study of his language through the many samples that Figaro brings us in his articles on customs. We finish with a chapter of conclusions to emphasize that Larra is a true genius in the practice of intelligent humor, understood as a variant close to black humor.